(untitled) ("Conference on Universal Science Research 2023", 2024)
This article explores the theory of compound sentences, focusing on both their structural and semantic types. It provides a detailed explanation of the various structural categories, such as coordinated, asyndetic, disjunctive, causal, and adversative compound sentences, illustrating how independent clauses are connected through different linguistic mechanisms. The article also delves into the semantic relationships between clauses, including additive, conditional, temporal, concessive, and resultative compound sentences, emphasizing how these structures convey specific meanings and logical connections. The analysis highlights the versatility of compound sentences in language, showing their importance in creating more complex and nuanced communication. This piece is an informative resource for understanding the grammatical and semantic intricacies of compound sentences, making it valuable for students, linguists, and language enthusiasts alike.